Ordinances: City of Des Moines, Weapons; Concealed, § 209, in H.W. Byers et al., Revised Ordinances of the City of Des Moines 1916, at 325 (1916) - (:unkn) unknown (My University, 1900)
Ordinances City of Des Moines, Weapons, Concealed, § 209: Prohibited the carrying of a concealed pistol or other firearms, slungshot, brass knuckles, or knuckles of lead, brass or other metal or material, or any sandbag, air guns of any description, dagger, Bowie knife, dirk knife, or other knife or instrument for cutting, stabbing or striking, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED